Magnitude of refractive errors in children in tertiary care hospital of western Nepal - Godar, Srijana Thapa (Journal of Chitwan Medical College, 2020)
Background: Refractive error is one of the most common causes of the visual impairment and second leading cause of treatable blindness. The objective of the study was to determine the magnitude of refractive errors in children. Methods: This was a hospital based cross-sectional study conducted on 254 children attending Ophthalmology OPD of Manipal Teaching Hospital, Pokhara. The children whose visual acuity was worse than 6/6 but improved with pinhole were included in this study. Vision test, retinoscopy and subjective refraction was done in all subjects and cycloplegic refraction was done when needed. Statistical analysis was carried out using Epi-info version 7. Results: The commonest type of refractive error was astigmatism (46.06%) followed by myopia (42.31%). Majority of children had low grade of refractive errors (46.85%). Among the children, “with the rule astigmatism” was maximum (27.56%). Majority of children were in the age between 11 to 15 years (77.95%). The refractive error was seen more in female (63.78%). Among the children of refractive errors, 29.13% had family history, 33.46% had given the history of wearing spectacles and 10.24% children had amblyopia. There was statistically significant association between refractive errors and age groups, history of wearing spectacles, amblyopia and grading of refractive errors. However, there was no statistically significant association of refractive error with gender, residence and family history. Conclusions: Astigmatism was the common type of refractive error followed by myopia. This study emphasizes the importance of detection of refractive error in children.